Comparing ANSYS Fluent® and OpenFOAM® simulations of Geldart A, B and D bubbling fluidized bed hydrodynamics. Issue 1 (25th September 2019) - Venier, Cesar Martin; Reyes Urrutia, Andrés; Capossio, Juan Pablo; Baeyens, Jan; Mazza, Germán
Abstract : Purpose: The purpose of this study is to assess the performance of ANSYS Fluent ® and OpenFOAM ®, at their current state of development, to study the relevant bubbling fluidized bed (BFB) characteristics with Geldart A, B and D particles. Design/methodology/approach: For typical Geldart B and D particles, both a three-dimensional cylindrical and a pseudo-two-dimensional arrangement were used to measure the bed pressure drop and solids volume fraction, the latter by digital image analysis techniques. For a typical Geldart A particle, specifically to examine bubbling and slugging phenomena, a 2 m high three-dimensional cylindrical arrangement of small internal diameter was used. The hydrodynamics of the experimentally investigated BFB cases were also simulated for identical geometries and operating conditions using OpenFOAM ® v6.0 and ANSYS Fluent ® v19.2 at identical mesh and numerical setups. Findings: The comparison between experimental and simulated results showed that both ANSYS Fluent ® and OpenFOAM ® provide a fair qualitative prediction of the bubble sizes and solids fraction for freely-bubbling Geldart B and D particles. For Geldart A particles, operated in a slugging mode, the qualitative predictions are again quite fair, but numerical values of relevant slug characteristics (length, velocity and frequency) slightly favor the use of OpenFOAM ®, despite some deviations of predicted slug velocities. Originality/value: A useful comparison of computational fluid dynamics (CFD) software performance for different fluidized regimes is presented. The results are discussed and recommendations are formulated for the selection of the CFD software and models involved.